Translocation (11;19)(q23;p13.3) associated with a novel t(5;16) (ql3;q22) in a patient with acute myelocytic leukemia - Vendrame-Goloni, C. B.; Varella-Garcia, M.; Carvalho-Salles, A. B.; Ruiz, M. A.; Ricci, O.; Fett-Conte, A. C. (Elsevier B.V., 2003)
A novel association of t(11;19)(q23;p13) and t(5;16)(q13;q22) was detected by G-banding and spectral karyotyping studies in an 18-year-old patient. While balanced t(11; 19) has been often described in acute myelocytic leukemia (AML) French-American-British Cooperative Group subtypes M4 and M5, this patient was diagnosed with the variant AML-M4 with eosinophilia (AML-M4Eo), which is associated with abnormalities in 16q22 and has good prognosis. However, the patient relapsed after allogeneic transplant and died within 2 years of diagnosis, which suggests that the association of these two translocations correlates with a poor prognosis. This report expands the molecular basis of the variability in clinical outcomes and adds the novel t(5;16)(q13;q22) to the spectrum of chromosome 16q22 abnormalities in AML. (C) 2003 Elsevier B.V. All rights reserved.